Model Kepemimpinan Islam yang Visioner dan Inovatif: The Model of Visionary and Innovative Islamic Leadership - Seema Manzoor (Society, 2023)
Globalization has changed the global scenario; it has converted the world into a global village, where we see a high sense of competition and contention between organizations at the national and international levels. A true leader with visionary qualities can play a vital role in bringing social change by administering effective characteristics. To attain true leadership qualities, a leader should rely completely on the sources of Islamic Law (Quran and Sunnah). This study explores the visionary and innovative Islamic leadership model to highlight various aspects of modern and professional life, especially focusing on natural tendencies and basic human needs linked with religion. This research has focused on qualitative methods by exploring the role of innovative Islamic leadership using various qualitative research techniques (library, research, and content analysis method) to establish an in-depth understanding of the people’s perspective of the visionary and innovative Islamic leadership model. This study examines the new dimension of Islamic leadership and attempts to capture an in-depth understanding based on the available literature about the research topic.